SUBJECTIVITY IN TIMES OF POST-TRUTH: CAPITALIST DISCOURSE IN THE PRODUCTION OF LANGUAGE, TRUTH, AND FACTS (Editora Impacto Científico, 2025)
This chapter aims to examine how different fake news stories disseminated on social media, the categories of language, facts, and realities that, even devoid of a sense of truth, articulate with capitalist ideology and engender new forms of contemporary subjectivities. The analysis seeks to identify the categories of language, the regimes of enunciation, and the pseudo-realities mobilized by these narratives, observing how such elements become capable of sustaining beliefs, affects, and forms of belonging. By exploring the dynamics between use value and exchange value in the context of fake news, it becomes evident that its effectiveness does not reside in the information itself, but in the way it circulates, how it captures attention, and how it is converted into symbolic commodities by digital capitalism, whose algorithmic functioning intensifies the logic of viralization. Furthermore, this chapter investigates the impacts of fake news on contemporary Brazilian social bonds, showing how these discourses contribute to the fragmentation of public space, affective polarization, and the construction of imaginary antagonisms that reorganize the political field. Finally, it seeks to understand how fake news participates in the production of identities and models of action today, establishing matrices of subjectivation that interpellate the subject, modulate their beliefs, and guide their social practices. Thus, it demonstrates that, in the hypermediated environment, fake news goes beyond the mere falsification of facts: it becomes a psychic and social device that shapes desires, perceptions, and ways of existing, occupying a central function in the subjective architecture of the contemporary world.DOI: https://doi.org/10.56238/edimpacto2025.090-083